Pemanfaatan Ekstrak Daun Jeruk Purut Sebagai Insektisida Alami Pembasmi Larva Instar III Culex sp - Rika Novera; Hasanuddin Hasanuddin; Safrida Safrida (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2017)
The use of chemicals as insecticides has caused resistance, health problems and environmental problems. Leaf extracts of Citus hystrix as a natural insecticide against Culex sp larvae can be used as an alternative to insecticides. This study aimed to determine the effect of kaffir lime leaf extract on mortality of third instar larvae of the mosquito Culex sp. This research approach is a quantitative approach. This type of research experiment with completely randomized design (CRD) comprised of 5 treatments and 4 replications. The treatment used is P0 (water wells) as a control, P1 (100 ppm concentration of the extract), P2 (250 ppm concentration of the extract), P3 (500 ppm concentration of the extract) and P4 (1000 ppm extract). The parameters of this study was mortality of larvae of Culex sp mosquitoes and seek LC50 and LC90. Data were analyzed using ANOVA (analysis of variants) and a further test Distance Real Duncan at significant level of 0.05. The results showed that the influence of kaffir lime leaf extract significant effect (P 0.05) against third instar larvae mortality of Culex sp. LC50 24 hours of kaffir lime leaf extract is 301,66 ppm. The conclusions of this research is to extract lime leaves significant effect on mortality of third instar Culex sp. Lime leaves extract showed the largest number of deaths there were 1000 ppm with a 100% mortality for 24 hours. Keywords: lime leaf, Culex sp,insecticide